2021
DOI: 10.1016/j.chaos.2021.111340
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging weather data for forecasting cases-to-mortality rates due to COVID-19

Abstract: There are several recent publications criticizing the failure of COVID-19 forecasting models, with swinging over predictions and underpredictions, which have made it difficult for decision and policy making. Observing the failures of several COVID-19 forecasting models and the alarming spread of the virus, we seek to use some stable response for forecasting COVID-19, viz., ratios of COVID-19 cases to mortalities, rather than COVID-19 cases or fatalities. A trend of low COVID-19 cases-to-mortality ratios calls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
4
1
Order By: Relevance
“…According to their study, only temperature was related to an increase in the prediction accuracy, and this increase was only detected in hot countries. The findings of Iloanusi and Ross (2021) do not align with those of previous studies, which indicated that temperature and humidity must be considered together. Moreover, temperature has been shown to improve the forecasting accuracy in cold countries, such as Canada ( Khennou and Akhloufi, 2021 ) and Russia ( Pramanik et al., 2020 ), and these results were rejected by Iloanusi and Ross (2021) .…”
Section: Literature Reviewcontrasting
confidence: 91%
See 3 more Smart Citations
“…According to their study, only temperature was related to an increase in the prediction accuracy, and this increase was only detected in hot countries. The findings of Iloanusi and Ross (2021) do not align with those of previous studies, which indicated that temperature and humidity must be considered together. Moreover, temperature has been shown to improve the forecasting accuracy in cold countries, such as Canada ( Khennou and Akhloufi, 2021 ) and Russia ( Pramanik et al., 2020 ), and these results were rejected by Iloanusi and Ross (2021) .…”
Section: Literature Reviewcontrasting
confidence: 91%
“…(2020) USA Shallow LSTM model UV, temperature, perception, ozone, dew, and humidity The prediction accuracy of the model was not affected by weather conditions data. Iloanusi and Ross (2021) 20 countries LSTM, random forest, Temperature, rainfall, windspeed, irradiation, humidity Temperature improved the accuracy of the forecasting models for most of the studied countries. Gupta et al.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…Several investigations have been conducted to build a COVID-19 prediction model. Iloanusi [25] developed an LSTM model and a random forest model to forecast the number of COVID-19 cases in 36 countries. They used a variety of data sources, namely COVID-19 case data from worldmeters.info and weather data obtained from the National Aeronautics and Space Administration (NASA).…”
Section: Methodsmentioning
confidence: 99%